STEAM Pedagogy as an Approach for Teacher Professional Development - Pant, Sanjaya Kumar; Luitel, Bal Chandra; Pant, Binod Prasad (Mathematics Education Forum Chitwan, 2020)
The ongoing in-service teacher learning or formal teacher professional development (TPD) is too conventional and de-escalating as the disciplinary skills and knowledge of teacher is insufficient to solve real world problems which are multi-disciplinary in origin. Thus, there is a critical need to explore and introduce multidisciplinary pedagogy with wise integration of science, technology, engineering, arts and mathematics (STEAM) concepts as an approach for TPD. This paper aims to explore the possible approaches of introducing STEAM pedagogy as an approach for TPD. This argumentative paper is prepared with the help of relevant and useful literatures. We argue the urgent need to integrate arts and technology in subject disciplines and design STEAM projects and training module as a neo-approach for TPD. This approach is equally useful for pre-service as well as in-service school teachers to develop multidisciplinary ways of knowing and solving real world problems.